2010
DOI: 10.1016/j.atmosenv.2010.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a CMAQ simulation at high resolution over the UK for the calendar year 2003

Abstract: A comprehensive ???operational??? evaluation of the performance of the Community Multiscale Air Quality (CMAQ) modelling system version 4.6 was conducted in support of pollution assessment in the UK for the calendar year 2003. The model was run on multiple grids using one-way nests down to a horizontal resolution as fine as 5 km over the whole of the UK. The model performance was evaluated for pollutants with standards and limit values (e.g. O3, PM10) and species contributing to acidic and nitrogenous depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 69 publications
4
37
0
1
Order By: Relevance
“…4b). Underestimation of measured nitrate wet deposition by models has also been reported by other authors (Dore et al, 2007;Chemel et al, 2010). The more complex chemical reactions associated with the formation of nitrate aerosol may mean that wet deposition of this chemical species is more difficult to simulate accurately than wet deposition of ammonium.…”
Section: Comparison Between Modeled and Measured Resultsmentioning
confidence: 68%
“…4b). Underestimation of measured nitrate wet deposition by models has also been reported by other authors (Dore et al, 2007;Chemel et al, 2010). The more complex chemical reactions associated with the formation of nitrate aerosol may mean that wet deposition of this chemical species is more difficult to simulate accurately than wet deposition of ammonium.…”
Section: Comparison Between Modeled and Measured Resultsmentioning
confidence: 68%
“…Baker and Scheff, 2007;Tesche et al, 2006;Gaydos et al, 2007;Mathur et al, 2008) using large scale measurement networks for their evaluation. There have been various modelling studies in Europe including comparisons with measured speciated aerosol such as Lazaridis et al (2005), Beekmann et al (2007), Chemel et al (2010), Renner and Wolke (2010), Lonati et al (2010), Andreani-Aksoyoglu et al (2011), Schaap et al (2011), Basart et al (2012) and Pay et al (2011). The modelling performance reported depends on component, season and location but the majority of these studies have reported an underestimation of observed concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Eulerian models, i.e. EMEP Vieno et al, 2010a) and CMAQ (Chemel et al, 2010) have more complex microphysical schemes for formation of rain and cloud but do not explicitly include a parameterisation of the seederfeeder effect. The representation of land cover and deposition to different vegetation types may vary between models and their applications.…”
Section: A J Dore Et Al: the Influence Of Model Grid Resolutionmentioning
confidence: 99%
“…This will therefore result in greater uncertainty in precipitation and therefore nitrogen deposition in the high rainfall regions, which also contain sensitive ecosystems. More complex Eulerian models (Vieno et al, 2010a;Chemel et al, 2010) dynamically generate precipitation with a meteorological model. However, modelled estimates of precipitation are known to be subject to considerable uncertainty.…”
Section: Precipitationmentioning
confidence: 99%
See 1 more Smart Citation